Aluminum foil, negative electrode for lithium secondary battery, separator for lithium secondary battery, and lithium secondary battery
By using a porous aluminum foil and an aluminum foil covering the Al-Li alloy layer in the lithium secondary battery, the problems of expansion and contraction of the aluminum foil and insufficient lithium ion permeability are solved, and the charge and discharge cycle characteristics of the lithium secondary battery and the battery are improved. Performance, achieving high energy density and high power density.
Patent Information
- Application Number
- CN202080074304.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-25
- Filing Date
- 2020-10-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-10-13
AI Technical Summary
The aluminum foil, the negative electrode material of the lithium secondary battery, is prone to expand and contract during the charging and discharging process, resulting in a decrease in the charging and discharging cycle characteristics, and the lithium ion permeability of the existing separators is insufficient, affecting the energy density and power density of the battery.
Using aluminum foil with porous regions as the negative electrode material and a separator, a continuous pore structure with complex communication in multiple pores throughout the thickness direction of the aluminum foil substrate is increased lithium ion conductivity, and on one or both sides of the aluminum foil substrate The Al-Li alloy layer is covered to improve lithium ion permeability.
It effectively suppresses the expansion and contraction of aluminum foil during charging and discharging, improves the charge and discharge cycle characteristics and battery characteristics of lithium secondary batteries, and achieves high energy density, high durability and high power battery performance.
Smart Images

Figure CN114616693B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium secondary battery. Background Art
[0002] As a high-power, high-energy-density secondary battery, a lithium secondary battery is widely used. The lithium secondary battery includes a positive electrode, a negative electrode, and an electrolyte solution, and is charged and discharged by transferring lithium ions between the positive electrode and the negative electrode.
[0003] As a negative electrode material for lithium secondary batteries, for example, aluminum that can absorb lithium by alloying with lithium is known (see, for example, Patent Document 1).
[0004] Therefore, aluminum foil can be used as the negative electrode of a lithium secondary battery, but the aluminum foil greatly expands and contracts during charge and discharge, so wrinkles, cracks, etc. may occur in the aluminum foil. As a result, for example, there is a problem that the charge and discharge cycle characteristics of the lithium secondary battery are reduced.
[0005] Furthermore, conventionally, a lithium secondary battery has a lithium ion permeable separator interposed between a positive electrode and a negative electrode.
[0006] Therefore, separators using materials capable of absorbing and storing lithium ions have been proposed (see, for example, Patent Documents 2 and 3). In Patent Document 2, aluminum foil is used for the separator, but the aluminum foil is nonporous and therefore has low lithium ion permeability.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: U.S. Patent No. 4002492
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 8-180853
[0011] Patent Document 3: Japanese Patent Application Publication No. 2010-219012 Summary of the invention
[0012] An aluminum foil as one embodiment of the present disclosure includes an aluminum foil base material having a porous region, wherein the porous region is formed over the entire thickness direction of the aluminum foil base material.
[0013] The aluminum foil of the present disclosure can suppress the reduction of the charge-discharge cycle characteristics when used as a negative electrode of a lithium secondary battery. In addition, the aluminum foil of the present disclosure has lithium ion permeability and can be used as a separator of a lithium secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic cross-sectional view showing an example of the aluminum foil according to the present embodiment.
[0015] Figure 2It is a schematic cross-sectional view showing another example of the aluminum foil according to the present embodiment.
[0016] Figure 3 This is a cross-sectional SEM photograph showing another example of the aluminum foil according to the present embodiment.
[0017] Figure 4 It is a figure which shows an example of the manufacturing apparatus of the aluminum foil which concerns on this embodiment.
[0018] Figure 5 It is a schematic cross-sectional view showing an example of the lithium secondary battery according to the present embodiment.
[0019] Figure 6 It is a schematic cross-sectional view showing an example of the lithium secondary battery according to the present embodiment.
[0020] Figure 7 This is a schematic cross-sectional view showing another example of a battery structure in which the aluminum foil of the present embodiment is used as a separator.
[0021] Figure 8 This is a schematic cross-sectional view showing another example of a battery structure in which the aluminum foil of the present embodiment is used as a separator. DETAILED DESCRIPTION
[0022] Hereinafter, an aluminum foil as one embodiment of the present invention, a lithium secondary battery using the aluminum foil as one embodiment of the present invention as a negative electrode, and an example of a lithium secondary battery using the aluminum foil as one embodiment of the present invention as a separator are described. The drawings referred to in the following description of the embodiments are schematic records, and the dimensional ratios of the components drawn in the drawings are sometimes different from the actual objects. In addition, in this specification, the description of "numerical value (1) to numerical value (2)" means greater than numerical value (1) and less than numerical value (2).
[0023] <Aluminum foil>
[0024] Figure 1A schematic cross-sectional view showing an example of the aluminum foil of the present embodiment. The aluminum foil 100 of the present embodiment has an aluminum foil substrate 100a having a porous region 100b. The porous region 100b is formed in the entire thickness direction of the aluminum foil substrate 100a. The porous region 100b has a plurality of continuous pores in the thickness direction that are complexly connected. It should be noted that all the pores present in the porous region 100b do not need to be completely connected, and may also include independent pores in a non-connected state. In any case, the electrolyte is immersed in the porous region 100b, and the lithium ions in the electrolyte pass through the porous region 100b. That is, the aluminum foil 100 of the present embodiment has ion permeability and can be used as a separator of a lithium secondary battery. In addition, if the aluminum foil 100 is used as the negative electrode of the lithium secondary battery, the absorption and storage of lithium ions is caused on the surface of the aluminum foil 100 and inside the porous region 100b during charging, and the absorbed and stored lithium ions are released during discharge. Then, the expansion and contraction of the aluminum foil 100 accompanying the storage and release of lithium ions is mitigated by the porous region 100b, thereby suppressing damage to the aluminum foil 100. As a result, the reduction in the charge and discharge cycle characteristics of the lithium secondary battery is suppressed compared to the aluminum foil 100 without the porous region 100b.
[0025] For example, a plurality of porous regions 100b are formed on the aluminum foil substrate 100a at intervals in the surface direction of the aluminum foil substrate 100a.
[0026] Preferably, the Al-Li alloy is present in the porous region 100b. Specifically, at least a portion of the aluminum foil substrate 100a in the porous region 100b becomes an Al-Li alloy. In this way, the Al-Li alloy is present in the porous region 100b, and the lithium ion conductivity of the porous region 100b becomes high. Therefore, when the aluminum foil 100 in which the Al-Li alloy is present in the porous region 100b is used as a negative electrode or a separator, the battery characteristics of the lithium secondary battery can be improved.
[0027] Figure 2 2 is a schematic cross-sectional view showing another example of the aluminum foil according to the present embodiment. Figure 3 FIG. 2 is a cross-sectional SEM photograph showing another example of the aluminum foil of the present embodiment. Figure 2 and Figure 3As shown, the aluminum foil 100 of the present embodiment has an Al-Li alloy layer 100c configured in a manner covering the porous region 100b on one side of the aluminum foil substrate 100a. In the aluminum foil 100 having such a structure, the electrolyte penetrates into the porous region 100b from one side of the aluminum foil substrate 100a and reaches the other side, but the solvent in the electrolyte is blocked by the Al-Li alloy layer 100c, so as a result, the aluminum foil 100 is basically not permeable. However, the lithium ions in the electrolyte can penetrate the Al-Li alloy layer 100c, so the aluminum foil 100 has lithium ion permeability. The description in the figure is omitted, but the aluminum foil 100 of the present embodiment can have an Al-Li alloy layer 100c configured in a manner covering the porous region 100b on both sides of the aluminum foil substrate 100a. Even in the case of having Al-Li alloy layer 100c on both sides, lithium ions also enter into porous region 100b through one Al-Li alloy layer 100c, and lithium ions in porous region 100b move outside porous region 100b through another Al-Li alloy layer 100c. Therefore, aluminum foil 100 having Al-Li alloy layer 100c configured in a manner covering porous region 100b on one or both sides of aluminum foil substrate 100a has ion permeability and can be used as a separator of lithium secondary battery. In addition, by using aluminum foil 100 having Al-Li alloy layer 100c configured in a manner covering porous region 100b on one or both sides of aluminum foil substrate 100a as negative electrode, porous region 100b can be effectively used as a reaction region with lithium, and therefore, battery characteristics are sometimes improved.
[0028] Therefore, in a lithium battery of a two-liquid system in which a positive electrode electrolyte is used in the electrolyte in contact with the positive electrode and a negative electrode electrolyte is used in the electrolyte in contact with the negative electrode, the best electrolyte can be used for the positive electrode and the negative electrode, respectively, so that the high energy density, high durability and high power of the lithium secondary battery can be achieved. In this two-liquid lithium battery, if a separator through which the solvent in the electrolyte is easy to pass is used, the solvent in the positive electrode electrolyte will move to the negative electrode side through the separator and be reduced and decomposed, and the solvent in the negative electrode electrolyte will move to the positive electrode side through the separator and be oxidized and decomposed, so the advantage of forming the electrolyte into two liquids cannot be obtained. However, in the case of the aluminum foil of the present embodiment, the porous region 100b is a continuous pore with a plurality of pores complexly connected in the thickness direction, so it becomes a structure through which the solvent in the electrolyte is not easy to pass. In particular, in the case of an aluminum foil 100 having an Al-Li alloy layer 100c disposed on one or both sides of an aluminum foil substrate 100a in a manner covering a porous region 100b, as described above, the solvent in the electrolyte is substantially unable to penetrate the aluminum foil 100. Therefore, the aluminum foil 100 of the present embodiment can isolate the positive electrode electrolyte from the negative electrode electrolyte, and thus can also be used as a separator for a two-liquid system lithium secondary battery. It should be noted that in conventional resin separators, the solvent in the electrolyte easily passes through the pores of the separator, and therefore it is difficult to isolate the positive electrode electrolyte from the negative electrode electrolyte.
[0029] When used as a separator or a negative electrode, the thickness of the aluminum foil substrate 100a can be appropriately set, for example, in order to ensure the strength and flexibility of the aluminum foil 100, preferably in the range of 1 μm to 200 μm, more preferably in the range of 5 μm to 150 μm.
[0030] When used as a separator or as a negative electrode, the average pore size of the pores constituting the porous region 100b can be appropriately set, for example, in order to ensure the strength and flexibility of the aluminum foil 100, preferably in the range of 0.0001 μm to 10 μm, and more preferably in the range of 0.001 μm to 5 μm.
[0031] The Al—Li alloy layer 100 c may be formed on the entirety of one surface or both surfaces of the aluminum foil substrate 100 a .
[0032] <Method for Manufacturing Aluminum Foil 100>
[0033] Figure 4 It is a schematic diagram which shows an example of the manufacturing apparatus of the aluminum foil which concerns on this embodiment. Figure 4The manufacturing device 1 shown includes: an electrolytic cell 13 having a first chamber 10 and a second chamber 11, electrolytes (14, 15) filled in the first chamber 10 and the second chamber 11, a counter electrode 16 immersed in the electrolyte 14 in the first chamber 10, and a counter electrode 17 immersed in the electrolyte 15 in the second chamber 11. The counter electrode 16 in the first chamber 10 and the counter electrode 17 in the second chamber 11 are lithium metal. The electrolytes (14, 15) filled in the first chamber 10 and the second chamber 11 contain a lithium salt and an organic solvent. The electrolytes (14, 15) filled in the first chamber 10 and the second chamber 11 may have the same composition or different compositions.
[0034] When manufacturing the aluminum foil of the present embodiment, an aluminum foil substrate 18 is disposed between the first chamber 10 and the second chamber 11 in such a manner that the first chamber 10 and the second chamber 11 are not connected, and the first chamber 10 and the second chamber 11 are filled with electrolytes (14, 15), and each electrode is disposed. That is, one surface of the aluminum foil substrate 18 is in contact with the electrolyte 14 of the first chamber 10, and the surface opposite to the one surface of the aluminum foil substrate 18 is in contact with the electrolyte 15 of the second chamber 11. Then, the counter electrode 16 of the first chamber 10 is electrically connected to the aluminum foil substrate 18, so that a reduction current flows in one surface of the aluminum foil substrate 18, and the counter electrode 17 of the second chamber 11 is electrically connected to the aluminum foil substrate 18, so that an oxidation current flows in the surface opposite to the one surface of the aluminum foil substrate 18. Thus, an Al-Li alloy is formed on one surface of the aluminum foil substrate 18 by a reduction current, and aluminum is dissolved on the surface opposite to the one surface of the aluminum foil substrate 18 by an oxidation current. By continuing the treatment for a predetermined time, a porous region is formed in the entire thickness direction of the aluminum foil substrate 18, and an Al-Li alloy is formed in the porous region, and then an Al-Li layer configured to cover the porous region is formed on one surface of the aluminum foil substrate 18. In addition, after a reduction current is made to flow in one surface of the aluminum foil substrate 18 to form an Al-Li alloy, a reduction current is made to flow in the surface opposite to the one surface of the aluminum foil substrate 18 to form an Al-Li alloy, thereby obtaining an aluminum foil having an Al-Li alloy layer formed on both surfaces of the aluminum foil substrate 18. It should be noted that, by only making an oxidation current flow in one surface of the aluminum foil substrate 18, an aluminum foil having a porous region formed in the entire thickness direction of the aluminum foil substrate 18 can also be obtained. Here, from the viewpoint of uniformity in the thickness direction of the porous region, it is preferred that an oxidation current flows simultaneously from both surfaces of the aluminum foil substrate 18.
[0035] The reduction current density on one surface of the aluminum foil substrate 18 is, for example, 1 μA / cm 2 ~100mA / cm 2 The oxidation current density on the surface opposite to one surface of the aluminum foil substrate 18 is, for example, 10 μA / cm 2 ~1000mA / cm 2In addition, the conduction time (processing time) of the reduction current and the oxidation current is, for example, in the range of 1 millisecond to 1000 hours.
[0036] The lithium salt contained in the electrolyte (14, 15) filled in the first chamber 10 and the second chamber 11 can use a known lithium salt used in the electrolyte of a lithium secondary battery, such as LiPF6. The organic solvent contained in the electrolyte (14, 15) filled in the first chamber 10 and the second chamber 11 can use a known organic solvent used in the electrolyte of a lithium secondary battery, such as cyclic carbonates such as propylene carbonate (PC), cyclic carboxylates such as γ-butyrolactone, and chain carboxylates such as methyl acetate.
[0037] <Lithium secondary battery using the aluminum foil of the present embodiment as a negative electrode>
[0038] Figure 5 It is a schematic cross-sectional view showing an example of the lithium secondary battery according to the present embodiment. Figure 5 The lithium secondary battery 20 shown comprises: a cup-shaped battery case 21; an electrode body having a positive electrode 22, a negative electrode 23, and a separator 24 arranged between the positive electrode 22 and the negative electrode 23; a gasket 25 formed of an insulating material; and a sealing plate 26 that seals the battery case 21 with the aid of the gasket 25 arranged at the opening of the battery case 21. Figure 5 The space between the positive electrode 22 and the negative electrode 23 of the lithium secondary battery 20 is filled with an electrolyte 27 . Figure 5 The lithium secondary battery 20 shown is called a so-called coin type or button type, but the form of the lithium secondary battery of this embodiment is not particularly limited, and may be, for example, cylindrical, flat, square, laminated, etc. In addition, the electrode body including the positive electrode 22, the negative electrode 23, and the separator 24 may be, for example, a wound electrode body in which the positive electrode and the negative electrode are wound with the separator interposed therebetween, or a laminated electrode body in which the positive electrode and the negative electrode are alternately laminated with the separator interposed therebetween.
[0039] The positive electrode 22 includes, for example, a positive electrode current collector and a positive electrode composite material layer formed on the positive electrode current collector. As the positive electrode current collector, a foil of a metal such as aluminum that is stable within the potential range of the positive electrode and a thin film having the metal disposed on the surface can be used. From the viewpoint of current collection, mechanical strength, etc., the thickness of the positive electrode current collector is preferably, for example, 3 μm or more and 50 μm or less.
[0040] The positive electrode composite material layer contains a positive electrode active material and may contain a binder, a conductive material, and the like.
[0041] As the positive electrode active material, for example, lithium transition metal oxides containing transition metal elements such as lithium (Li), cobalt (Co), manganese (Mn) and nickel (Ni) can be cited. As the positive electrode active material, in addition, transition metal sulfides, metal oxides, lithium iron phosphate (LiFePO4), lithium iron pyrophosphate (Li2FeP2O7) and other lithium-containing polyanion compounds containing one or more transition metals, sulfur compounds (Li2S), oxygen, lithium oxide and other oxygen-containing metal salts can also be cited. As the positive electrode active material, preferably lithium-containing transition metal oxides, as the transition metal element, preferably contain at least one of Co, Mn and Ni.
[0042] Lithium transition metal oxides may contain other added elements besides Co, Mn and Ni, for example, aluminum (Al), zirconium (Zr), boron (B), magnesium (Mg), scandium (Sc), yttrium (Y), titanium (Ti), iron (Fe), copper (Cu), zinc (Zn), chromium (Cr), lead (Pb), tin (Sn), sodium (Na), potassium (K), barium (Ba), strontium (Sr), calcium (Ca), tungsten (W), molybdenum (Mo), niobium (Nb) and silicon (Si), etc.
[0043] Specific examples of lithium transition metal oxides include Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (in each chemical formula, M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb and B, and is 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). Lithium transition metal oxides can be used alone or in combination. From the viewpoint of high capacity, lithium transition metal oxides preferably contain more than 80 mol% Ni relative to the total amount of transition metals other than lithium. In addition, from the viewpoint of the stability of the crystal structure, lithium transition metal oxides are more preferably Li a Ni b Coc Al d O2 (0<a≤1.2, 0.8≤b<1, 0<c<0.2, 0<d≤0.1, b+c+d=1).
[0044] As a conductive material, a known conductive material that improves the conductivity of the positive electrode composite material layer can be used, for example, carbon black, acetylene black, Ketjen black, graphite, carbon nanofiber, carbon nanotube, graphene and other carbon materials can be cited. As a binding material, a known binding material that maintains the good contact state of the positive active material and the conductive material, and improves the bonding of the positive active material and the positive current collector surface can be used, for example, fluororesins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), etc. can be cited.
[0045] The positive electrode 22 can be manufactured, for example, by applying a positive electrode composite material slurry containing a positive electrode active material, a binder, a conductive material, etc., on a positive electrode current collector, and drying and rolling the coating to form a positive electrode composite material layer on the positive electrode current collector.
[0046] The negative electrode 23 uses the aluminum foil of the present embodiment. That is, the negative electrode 23 uses an aluminum foil having an aluminum foil substrate having a porous region formed in the entire thickness direction. As mentioned above, the expansion and contraction accompanying the absorption, storage and release of lithium ions are alleviated by the porous region formed in the aluminum foil substrate, so the damage of the negative electrode 23 (aluminum foil) is suppressed. As a result, the reduction of the charge and discharge cycle characteristics of the lithium secondary battery 20 is suppressed.
[0047] In addition, it is preferable that the Al-Li alloy exists in the porous region. As a result, the lithium ion conductivity of the porous region becomes higher, so the battery characteristics of the lithium secondary battery 20 may be improved. Specifically, the initial capacity of the lithium secondary battery may be improved.
[0048] In addition, it is preferred to configure an Al-Li alloy layer on one or both sides of the aluminum foil substrate in a manner that covers the porous region. As a result, the porous region can be effectively used as a reaction region with lithium, and thus the battery characteristics are sometimes improved. Specifically, the initial capacity of the lithium secondary battery is sometimes improved. Using an aluminum foil having an Al-Li alloy layer on one side of the aluminum foil substrate as a negative electrode, using Li x When a lithium transition metal oxide such as CoO2 is used as the positive electrode active material, the negative electrode (aluminum foil) is preferably arranged so that the surface of the aluminum foil substrate without the Al-Li alloy layer is opposite to the positive electrode 22 via the separator 24. As a result, lithium ions become easier to move in the porous region, and the battery characteristics are sometimes improved.
[0049] In order to improve battery characteristics while ensuring the strength and flexibility of the aluminum foil, the thickness of the aluminum foil base is preferably in the range of 10 μm to 200 μm, and more preferably in the range of 50 μm to 150 μm, for example.
[0050] In order to improve battery characteristics while ensuring the strength and flexibility of the aluminum foil, the average pore diameter of the pores constituting the porous region is, for example, preferably in the range of 0.1 μm to 10 μm, more preferably in the range of 0.5 μm to 5 μm.
[0051] The separator 24 uses, for example, a porous sheet that allows lithium ions to pass through. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. As the material of the porous sheet, olefin resins such as polyethylene and polypropylene, polyamide, polyamide-imide, cellulose, etc. can be mentioned. The porous sheet can be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. In addition, it can also be a multilayer body including a polyethylene layer and a polypropylene layer, and it can also be used to apply an aramid resin, ceramics, etc. on the surface of the porous sheet. It should be noted that the separator 24 can use the aluminum foil of the present embodiment as described later.
[0052] The electrolyte solution contains a solvent and an electrolyte salt dissolved in the solvent. In addition, a gel electrolyte such as a gel polymer may be used instead of the electrolyte solution.
[0053] Examples of the solvent include carbonates, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof. The solvent may also contain a halogen-substituted product obtained by replacing at least a portion of hydrogen atoms of these solvents with halogen atoms such as fluorine.
[0054] Examples of the above-mentioned esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate, chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate, cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL), and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.
[0055] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether. , dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.
[0056] As the halogen-substituted product, fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as fluoromethyl propionate (FMP), and the like are preferably used.
[0057] Electrolyte salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 、Lithium lower aliphatic carboxylates、LiCl、LiBr、LiI、Li(P(C2O4)F4)、LiPF 6-x (C n F 2n+1)x (1<x<6, n is 1 or 2), lithium chloroborane, borates, imide salts, etc. Examples of borates include Li[B(C2O4)2], Li[B(C2O4)F2], Li2B4O7, bis(1,2-benzenediol (2-)-O,O') lithium borate, bis(2,3-naphthalenediol (2-)-O,O') lithium borate, bis(2,2'-biphenylediol (2-)-O,O') lithium borate, and bis(5-fluoro-2-ol-1-benzenesulfonic acid-O,O') lithium borate. As imide salts, for example, bis(trifluoromethanesulfonyl)imide lithium (LiTFSI), bis(perfluoroethanesulfonyl)imide lithium (LiBETI), (perfluoroethanesulfonyl) (trifluoromethanesulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium (LiFSI), (fluorosulfonyl) (trifluoromethanesulfonyl)imide lithium (LiFTI), etc. can be cited. Among them, in terms of battery characteristics, LiPF6, LiTFSI, LiBF4, LiSbF6, LiCF3SO3, LiCF3CO2 are preferred. The electrolyte salt can be used alone or in combination. The concentration of the electrolyte salt is preferably 0.5 to 3 mol / L, and more preferably 0.8 to 1.8 mol / L.
[0058] <Lithium secondary battery using the aluminum foil of the present embodiment as a separator>
[0059] Figure 6 It is a schematic cross-sectional view showing an example of the lithium secondary battery according to the present embodiment. Figure 6 The lithium secondary battery 30 shown includes a positive electrode 32 , a negative electrode 33 , a separator 34 disposed to space the positive electrode 32 and the negative electrode 33 , a positive electrode electrolyte 36 , a negative electrode electrolyte 38 , and a storage container 40 .
[0060] Figure 6 In the lithium secondary battery 30 shown, the storage container 40 is separated into a positive electrode chamber 42 and a negative electrode chamber 44 by a separator 34. The positive electrode chamber 42 contains the positive electrode 32 and the positive electrode electrolyte 36, and the negative electrode chamber 44 contains the negative electrode 33 and the negative electrode electrolyte 38.
[0061] The positive electrode 32 includes, for example, a positive electrode current collector and a positive electrode composite material layer formed on the positive electrode current collector. As the positive electrode current collector, a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 32, and a thin film having the metal disposed on the surface layer can be used. From the viewpoint of current collection, mechanical strength, etc., the thickness of the positive electrode current collector is preferably, for example, 3 μm or more and 50 μm or less.
[0062] The positive electrode composite material layer contains a positive electrode active material and may contain a binder, a conductive material, and the like.
[0063] As the positive electrode active material, for example, lithium transition metal oxides containing transition metal elements such as lithium (Li), cobalt (Co), manganese (Mn) and nickel (Ni) can be cited. As the positive electrode active material, transition metal sulfides, metal oxides, lithium iron phosphate (LiFePO4), lithium iron pyrophosphate (Li2FeP2O7) and other lithium-containing polyanion compounds containing more than one transition metal, sulfur compounds (Li2S), oxygen, lithium oxide and other oxygen-containing metal salts can also be cited. As the positive electrode active material, preferably lithium-containing transition metal oxides, as the transition metal element, preferably contain at least one of Co, Mn and Ni.
[0064] Lithium transition metal oxides may contain other added elements besides Co, Mn and Ni, for example, aluminum (Al), zirconium (Zr), boron (B), magnesium (Mg), scandium (Sc), yttrium (Y), titanium (Ti), iron (Fe), copper (Cu), zinc (Zn), chromium (Cr), lead (Pb), tin (Sn), sodium (Na), potassium (K), barium (Ba), strontium (Sr), calcium (Ca), tungsten (W), molybdenum (Mo), niobium (Nb) and silicon (Si), etc.
[0065] Specific examples of lithium transition metal oxides include Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (in each chemical formula, M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb and B, and is 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). Lithium transition metal oxides can be used alone or in combination. From the viewpoint of high capacity, lithium transition metal oxides preferably contain more than 80 mol% Ni relative to the total amount of transition metals other than lithium. In addition, from the viewpoint of the stability of the crystal structure, lithium transition metal oxides are more preferably Li a Ni b Co cAl d O2 (0<a≤1.2, 0.8≤b<1, 0<c<0.2, 0<d≤0.1, b+c+d=1).
[0066] As a conductive material, a known conductive material that improves the conductivity of the positive electrode composite material layer can be used, for example, carbon black, acetylene black, Ketjen black, graphite, carbon nanofiber, carbon nanotube, graphene and other carbon materials can be cited. As a binding material, a known binding material that maintains the good contact state of the positive active material and the conductive material, and improves the bonding of the positive active material and the positive current collector surface can be used, for example, fluororesins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), etc. can be cited.
[0067] The positive electrode 32 can be manufactured, for example, by applying a positive electrode composite material slurry containing a positive electrode active material, a binder, a conductive material, etc., on a positive electrode current collector, and drying and rolling the coating to form a positive electrode composite material layer on the positive electrode current collector.
[0068] The negative electrode 33 includes, for example, a negative electrode current collector and a negative electrode composite material layer formed on the negative electrode current collector. As the negative electrode current collector, a foil of a metal such as copper that is stable within the potential range of the negative electrode 33 and a thin film having the metal disposed on the surface can be used. From the viewpoint of current collection, mechanical strength, etc., the thickness of the negative electrode current collector is preferably, for example, 3 μm or more and 50 μm or less.
[0069] The negative electrode composite material layer contains a negative electrode active material. In addition, the negative electrode composite material layer may contain a binder, a conductive material, etc. The conductive material and the binder may be the same as those on the positive electrode 32 side.
[0070] As the negative electrode active material, for example, carbonaceous materials such as natural graphite, artificial graphite, soft carbon, hard carbon and other amorphous carbon can be cited. As the negative electrode active material, as long as it is a material that can absorb and release lithium ions, in addition to carbonaceous materials, for example, elements such as silicon, titanium, germanium, tin, lead, zinc, magnesium, sodium, aluminum, potassium, indium, alloys, or oxides can be cited.
[0071] The negative electrode 33 can be manufactured, for example, by applying a negative electrode composite material slurry containing a negative electrode active material, a binding material, etc., to a negative electrode collector, drying and rolling the coating to form a negative electrode composite material layer on the negative electrode collector. Alternatively, a lithium metal foil can be bonded to the negative electrode collector.
[0072] The separator 34 uses the aluminum foil of this embodiment. That is, the separator 34 uses an aluminum foil having an aluminum foil substrate having a porous region formed in the entire thickness direction. As described above, lithium ions pass through the porous region formed in the aluminum foil substrate. Therefore, during charging and discharging, lithium ions can be moved between the positive electrode 32 and the negative electrode 33 through the aluminum foil as the separator 34.
[0073] In addition, the porous area formed in the aluminum foil substrate becomes a continuous pore with multiple pores complexly connected in the thickness direction, thereby preventing the positive electrode electrolyte 36 from moving to the negative electrode chamber 44 side through the separator 34 (aluminum foil), or the negative electrode electrolyte 38 from moving to the positive electrode chamber 42 side through the separator 34 (aluminum foil).
[0074] In addition, it is preferable that the Al-Li alloy exists in the porous region. As a result, the lithium ion conductivity of the porous region becomes high, so the battery characteristics of the lithium secondary battery 30 may be improved. Specifically, the initial capacity of the lithium secondary battery 30 may be improved.
[0075] In addition, preferably, Al-Li alloy layer is configured in a way of covering porous region on one side or both sides of aluminum foil substrate.For example, in the case of Al-Li alloy layer formed on one side of aluminum foil substrate, even if electrolyte invades in porous region from one side of aluminum foil substrate that has never formed Al-Li alloy layer, and reaches the other side formed with Al-Li alloy layer, solvent in electrolyte is also blocked by Al-Li alloy layer, so as a result, it is basically impossible to penetrate separator 34 (aluminum foil). In addition, in the case of Al-Li alloy layer formed on both sides of aluminum foil substrate, solvent in electrolyte is basically unable to invade in porous region.Therefore, by using aluminum foil as separator 34 formed with Al-Li alloy layer configured in a way of covering porous region on one side or both sides of aluminum foil substrate, it is possible to more effectively suppress positive electrode electrolyte 36 to move to negative electrode chamber 44 side across separator 34 or negative electrode electrolyte 38 to move to positive electrode chamber 42 side across separator 34.
[0076] In this way, by suppressing the movement of the negative electrode electrolyte 38 and the positive electrode electrolyte 36 across the separator 34, the reduction decomposition of the electrolyte at the negative electrode chamber 44 side and the oxidation decomposition of the electrolyte at the positive electrode chamber 42 side are suppressed, and thus, the occurrence of side reactions associated with charging and discharging is suppressed. Thus, the high energy density, high durability, and high power of the lithium secondary battery 30 can be achieved. It should be noted that, from the perspective of good compatibility with the electrolyte and difficulty in forming complex continuous pores, the previous resin separator cannot fully suppress the movement of the electrolyte, and therefore cannot obtain the advantage of forming the electrolyte into two liquids.
[0077] For example, in order to ensure the strength and flexibility of the aluminum foil while ensuring lithium ion permeability or suppressing the migration of the solvent in the electrolyte, the thickness of the aluminum foil substrate is preferably in the range of 1 μm to 200 μm, more preferably in the range of 5 μm to 20 μm.
[0078] For example, in order to ensure the strength and flexibility of the aluminum foil while ensuring lithium ion permeability or inhibiting the movement of the solvent in the electrolyte, the average pore size of the pores constituting the porous region is preferably in the range of 0.0001 μm to 10 μm, and more preferably in the range of 0.001 μm to 2 μm.
[0079] When the aluminum foil of the present embodiment is used as the separator 34 , the positive electrode 32 and the negative electrode 33 need to be separated from the separator 34 so that the positive electrode 32 and the negative electrode 33 are not electrically connected to each other via the separator 34 .
[0080] The positive electrode electrolyte 36 and the negative electrode electrolyte 38 in this embodiment may have the same composition, but preferably have the best electrolyte composition to achieve high energy density, high durability, and high power. The following is an example of the composition suitable for the positive electrode electrolyte 36 and the negative electrode electrolyte 38.
[0081] The solvent used in the positive electrode electrolyte 36 is preferably, for example, + ) is higher than the oxidation potential (relative to Li / Li + ), for example, preferably about 0.5 V to 2.0 V higher. Furthermore, the solvent used in the positive electrode electrolyte 36 is more preferably + ) is higher than the full charge potential of the positive electrode active material (relative to Li / Li + ), for example, more preferably than the full charge potential (relative to Li / Li + ) is higher by 0.2 V or more. Thus, oxidative decomposition of the positive electrode electrolyte 36 in the positive electrode 32 can be more highly suppressed.
[0082] As the solvent used in the positive electrode electrolyte 36, for example, preferably cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate, chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate, cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL), chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate, fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates such as dimethyl trifluorocarbonate (TFDMC), and fluorinated chain carboxylates such as methyl fluoropropionate (FMP).
[0083] The solvent used in the negative electrode electrolyte 38 is preferably a solvent that does not easily cause reductive decomposition in the negative electrode 33. For example, 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ether, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, Ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.
[0084] The electrolyte salts used in the positive electrode electrolyte 36 and the negative electrode electrolyte 38 may be the same or different as long as they are lithium salts commonly used in lithium secondary batteries. Examples thereof include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 、Lithium lower aliphatic carboxylates、LiCl、LiBr、LiI、Li(P(C2O4)F4)、LiPF 6-x (C n F 2n+1 )x (1<x<6, n is 1 or 2), lithium chloroborane, borates, imide salts, etc. Examples of borates include Li[B(C2O4)2], Li[B(C2O4)F2], Li2B4O7, bis(1,2-benzenediol (2-)-O,O') lithium borate, bis(2,3-naphthalenediol (2-)-O,O') lithium borate, bis(2,2'-biphenylediol (2-)-O,O') lithium borate, and bis(5-fluoro-2-ol-1-benzenesulfonic acid-O,O') lithium borate. Examples of imide salts include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(perfluoroethanesulfonyl)imide (LiBETI), lithium (perfluoroethanesulfonyl)(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide (LiFSI), and lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide (LiFTI). The electrolyte salts may be used alone or in combination.
[0085] The concentration of the electrolyte salt in the positive electrode electrolyte 36 is preferably 0.5 mol / L to 3.0 mol / L, more preferably 0.8 mol / L to 1.8 mol / L. The concentration of the electrolyte salt in the negative electrode electrolyte 38 is preferably 0.5 mol / L to 3.0 mol / L, more preferably 0.8 mol / L to 1.8 mol / L.
[0086] Modifications of the battery structure when the aluminum foil of the present embodiment is used as a separator are described below.
[0087] Figure 7 2 is a schematic cross-sectional view showing another example of a battery structure when the aluminum foil of this embodiment is used as a separator. For the lithium secondary battery of this embodiment, instead of the above-mentioned positive electrode electrolyte and negative electrode electrolyte, the following can be used: Figure 7 The battery structure shown has a positive electrode gel electrolyte layer 46 disposed between the positive electrode 32 and the separator 34 which is the aluminum foil of the present embodiment, and a negative electrode gel electrolyte layer 48 disposed between the negative electrode 33 and the separator 34 which is the aluminum foil of the present embodiment. The thickness of the positive electrode gel electrolyte layer 46 and the negative electrode gel electrolyte layer 48 is, for example, about 5 μm to 100 μm.
[0088] The positive electrode gel electrolyte layer 46 can be formed, for example, by applying a precursor solution containing a polymer precursor, a polymerization initiator, etc., to the positive electrode composite material layer, and then allowing the polymerization reaction to proceed under appropriate conditions and gelation. The negative electrode gel electrolyte layer 48 can also be formed in the same manner.
[0089] The polymerization temperature during gelation can be appropriately selected, for example, it can be set to about 80 to 140° C. The polymerization time can also be appropriately selected, for example, it can be set to about 5 minutes to 3 hours. It should be noted that the so-called "polymerization reaction" here can be any reaction that is conducive to the gelation (hardening) of the above-mentioned precursor solution, such as a cross-linking reaction, a condensation reaction, etc.
[0090] The polymer precursor may be a multifunctional polymer precursor or a monofunctional polymer precursor, and preferably a polymer precursor (multifunctional polymer precursor) having two or more polymerizable (crosslinkable) functional groups. Specifically, ethylene oxide (EO), propylene oxide (PO), acrylonitrile (AN), vinylidene fluoride (VDF), etc. are mentioned. Typically, a polymer precursor having a thermally polymerizable (thermally crosslinkable) functional group is used.
[0091] The polymerization initiator can be appropriately selected and used according to the type of polymer precursor used. Typically, a thermal polymerization initiator is used. As the thermal polymerization initiator, various initiators known in the past such as azo series and peroxide series can be used. As preferred polymerization initiators, azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO) and the like can be exemplified.
[0092] Figure 8 2 is a schematic cross-sectional view showing another example of a battery structure when the aluminum foil of this embodiment is used as a separator. Figure 8 As shown, a porous sheet 50 can be configured between the positive electrode 32 and the separator 34 of the aluminum foil as the present embodiment and between the negative electrode 33 and the separator 34 of the aluminum foil as the present embodiment. The porous sheet 50 is expected to have high electrical insulation and a function of allowing lithium ions to pass through. As specific examples of the porous sheet 50, microporous films, woven fabrics, non-woven fabrics, etc. can be cited. As the material of the porous sheet 50, olefin resins such as polyethylene and polypropylene, polyamide, polyamide-imide, cellulose, etc. can be cited. The porous sheet 50 can be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. In addition, it can also be a multilayer body comprising a polyethylene layer and a polypropylene layer, and it can also be a person formed by coating the surface of the porous sheet 50 with materials such as aramid resins and ceramics.
[0093] The positive electrode electrolyte may be impregnated into the porous sheet 50 disposed between the positive electrode 32 and the separator 34 of the aluminum foil of the present embodiment. The negative electrode electrolyte may be impregnated into the porous sheet 50 disposed between the negative electrode 33 and the separator 34 of the aluminum foil of the present embodiment.
[0094] In addition, the positive electrode composite material layer constituting the positive electrode 32 preferably comprises a clay-like wet film of a positive electrode active material, a binding material, a conductive material, and the aforementioned positive electrode electrolyte. The positive electrode composite material layer can be obtained by applying a positive electrode composite material slurry comprising a positive electrode active material, a binding material, a conductive material, a positive electrode electrolyte, etc., to a positive electrode collector. The negative electrode composite material layer constituting the negative electrode 33 also preferably comprises a clay-like wet film of a negative electrode active material, a binding material, and a negative electrode electrolyte. The negative electrode composite material layer can be obtained by applying a negative electrode composite material slurry comprising a negative electrode active material, a binding material, a negative electrode electrolyte, etc., to a negative electrode collector.
[0095] <Example>
[0096] Hereinafter, the present disclosure will be further described by way of examples, but the present disclosure is not limited to these examples.
[0097] [Manufacturing of aluminum foil]
[0098] use Figure 4 The manufacturing apparatus shown was used to flow an oxidation current on both surfaces of an aluminum foil substrate having a thickness of 12 μm under the following conditions.
[0099] Electrolyte: LiTFSI / PC=1 / 10 (molar ratio)
[0100] Oxidation current density: 10μA / cm 2
[0101] Processing time: 1 hour
[0102] The cross section of the treated aluminum foil substrate was observed by SEM, and it was confirmed that a porous region was formed over the entire thickness direction of the aluminum foil substrate.
[0103] use Figure 4 In the manufacturing apparatus shown, a reduction current is passed through one surface of an aluminum foil substrate, and an oxidation current is passed through the other surface opposite to the one surface under the following conditions.
[0104] Electrolyte: LiTFSI / PC=1 / 10 (molar ratio)
[0105] Reduction current density: 10μA / cm 2
[0106] Oxidation current density: 10μA / cm 2
[0107] Processing time: 332 hours
[0108] The cross section of the aluminum foil substrate after treatment was confirmed by SEM, and the result confirmed that a porous region was formed in the entire domain of the thickness direction of the aluminum foil substrate. In addition, a covering layer configured in a manner covering the porous region was confirmed on the other side of the aluminum foil substrate. The components in the covering layer and the porous region were confirmed by Auger electron spectroscopy, and the result confirmed that the covering layer was formed by an Al-Li alloy and contained an Al-Li alloy in the porous region. This was used as aluminum foil B.
[0109] <Example 1>
[0110] [negative electrode]
[0111] The aluminum foil A was cut into a predetermined electrode size and used as a negative electrode.
[0112] [positive electrode]
[0113] In NMP, LiCoO2 as a positive electrode active material, carbon black as a conductive material, and PVdF as a binder were mixed in a mass ratio of 94:3:3 to prepare a positive electrode composite material slurry. Next, the positive electrode composite material slurry was applied to a positive electrode collector formed of Al foil, and after the coating was dried, it was rolled using a roller. Then, it was cut into a specified electrode size to obtain a positive electrode.
[0114] [Electrolyte]
[0115] A solution in which LiPF6 and PC were mixed at a molar ratio of LiPF6 / PC=1 / 10 was used as an electrolyte.
[0116] [Test battery cell]
[0117] The electrode bodies in which the positive electrode and the negative electrode were arranged to face each other via a polypropylene separator (manufactured by Celgard, #3401) and the electrolyte were housed in a cup-shaped battery case, and the battery case was sealed with a sealing plate via a gasket arranged at the opening of the battery case to prepare a test battery cell.
[0118] <Example 2>
[0119] A test cell was prepared in the same manner as in Example 1 except that the aluminum foil B was cut into a predetermined size and used as a negative electrode.
[0120] <Comparative Example 1>
[0121] A test cell was prepared in the same manner as in Example 1 except that an aluminum foil substrate without a porous region was used as the negative electrode.
[0122] [Charge and discharge test]
[0123] The test battery cells of Examples 1 and 2 and Comparative Example 1 were charged at a constant current of 0.01 C until the battery voltage reached 4.3 V in an environment of 25° C. Then, they were discharged at a constant current of 0.01 C until the battery voltage reached 2.5 V. This charge and discharge cycle was repeated 20 times.
[0124] The charge and discharge efficiency ((discharge capacity / charge capacity)×100) of the 20th cycle is as follows: 93.1% for Example 1, 93.3% for Example 2, and 92.4% for Comparative Example 1. From these results, Examples 1 and 2 using an aluminum foil having a porous region formed in the entire thickness direction of the aluminum foil substrate as the negative electrode can suppress the reduction of the charge and discharge cycle characteristics compared to Comparative Example 1 using an aluminum foil having no porous region formed as the negative electrode.
[0125] In addition, the initial charge and discharge efficiency is as follows: 74.7% for Example 1, 74.8% for Example 2, and 74.4% for Comparative Example 1. From these results, as in Example 2, the use of an aluminum foil as a negative electrode in which an Al-Li alloy exists in a porous region and an Al-Li alloy layer is arranged on one side of an aluminum foil substrate so as to cover the porous region can improve the initial charge and discharge efficiency.
[0126] <Example 3>
[0127] exist Figure 4 The two chambers of the manufacturing device shown were filled with an electrolyte solution of LiTFSI / PC = 1 / 10 (molar ratio) and a current of 1 mA / cm 2 An oxidation current of 1000 W was passed through both surfaces of an aluminum foil having a thickness of 12 μm for 1 second, thereby obtaining an aluminum foil C having a porous region throughout the entire thickness direction.
[0128] like Figure 6 As shown, a test battery cell is prepared in which a storage container is separated into a positive electrode chamber and a negative electrode chamber by a separator, a positive electrode (working electrode) and a positive electrode electrolyte are stored in the positive electrode chamber, and a negative electrode (counter electrode) and a negative electrode electrolyte are stored in the negative electrode chamber. The separator uses the above-mentioned aluminum foil C. In addition, a platinum mesh electrode is used for the positive electrode, and a lithium metal electrode is used for the negative electrode. In addition, the electrolyte used for the positive electrode is an electrolyte in which LiTFSI is dissolved in a manner of 10 moles to 1 mole relative to a solvent of propylene carbonate (PC), and the electrolyte used for the negative electrode is an electrolyte in which LiTFSI is dissolved in a manner of 10 moles to 1 mole relative to a solvent of diethylene glycol dimethyl ether (diglyme).
[0129] <Example 4>
[0130] exist Figure 4 The two chambers of the manufacturing apparatus shown were filled with an electrolyte solution of LiTFSI / PC = 1 / 10 (molar ratio) and a current of 1 mA / cm 2 A reduction current of 1 mA / cm2 flows on one side of a 12 μm thick aluminum foil. 2 An oxidation current of 10000 was passed on the other surface for 10 hours, thereby obtaining aluminum foil D having a porous region throughout the thickness direction and an Al-Li alloy layer. A test cell was prepared in the same manner as in Example 3 except that aluminum foil D was used as a separator.
[0131] <Comparative Example 2>
[0132] A test cell was prepared in the same manner as in Example 3 except that a polypropylene separator (manufactured by Celgard, #3401) was used.
[0133] In the test cells of Examples 3 and 4 and Comparative Example 2, a voltage of 4.3 V was applied between the positive electrode (working electrode) and the negative electrode (counter electrode) for 50 hours, and the current value flowing between the positive electrode and the negative electrode was measured. As a result, in the test cells of Examples 3 and 4, the current value varied below 0.1 μA, but in the test cell of Comparative Example 2, the current value varied around 0.6 μA.
[0134] In addition, in the test cells of Examples 3, 4 and Comparative Example 2, a voltage of 4.5 V was applied between the positive electrode (working electrode) and the negative electrode (counter electrode) for 50 hours, and the current value between the two electrodes was measured. As a result, in the test cell of Example 3, the current value was 0.2 μA, in the test cell of Example 4, the current value was 0.18 μA or less, but in the test cell of Comparative Example 2, the current value was about 1 μA.
[0135] In addition, in the test cells of Examples 3, 4 and Comparative Example 2, a voltage of 4.7 V was applied between the positive electrode (working electrode) and the negative electrode (counter electrode) for 100 hours, and the current value between the two electrodes was measured. As a result, in the test cell of Example 3, the current value was 0.25 μA, in the test cell of Example 4, the current value was 0.2 μA or less, but in the test cell of Comparative Example 2, the current value was about 6 μA.
[0136] In this way, in Examples 3 and 4, in which an aluminum foil having a porous area formed in the entire thickness direction of the aluminum foil substrate is used as a separator, the current value between the two poles is shifted at a very low value even when a high voltage is applied. According to the results, it can be considered that in Examples 3 and 4, the solvent in the negative electrode electrolyte in the negative electrode chamber is suppressed from moving to the positive electrode chamber through the separator, and the oxidative decomposition of the electrolyte in the positive electrode chamber is basically not carried out. Thus, high energy density, high durability, and high power of lithium secondary batteries can be achieved. On the other hand, compared with Examples 3 and 4, in Comparative Example 2 using a polypropylene separator, the current value between the two poles is shifted at a high value when a high voltage is applied. According to the results, it can be considered that in Comparative Example 2, the solvent in the negative electrode electrolyte in the negative electrode chamber cannot be suppressed from moving to the positive electrode chamber through the separator, and the oxidative decomposition of the electrolyte in the positive electrode chamber is carried out compared with Examples 3 and 4.
[0137] It should be noted that in Examples 3 and 4, the platinum mesh was replaced with LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2 is an electrode (positive electrode) with positive electrode active material. In addition, the positive electrode electrolyte is replaced with a LiPF6 / PC=1 / 10 (molar ratio) solution. As a result, a charge-discharge reaction with the movement of lithium ions between the positive electrode and the negative electrode is confirmed (voltage range: 2.5-4.7 V). That is, the aluminum foil used in Examples 3 and 4 has lithium ion permeability and can be used as a separator.
[0138] Description of Reference Numerals
[0139] 1. Manufacturing device
[0140] 10Room 1
[0141] 11Room 2
[0142] 13Electrolyzer
[0143] 14.15 Electrolyte
[0144] 16, 17 pairs of electrodes
[0145] 18 Aluminum foil substrate
[0146] 20,30 lithium secondary battery
[0147] 21 Battery housing
[0148] 22, 32 positive electrode
[0149] 23, 33 negative electrode
[0150] 24, 34 separators
[0151] 25 gasket
[0152] 26 Sealing plate
[0153] 27 Electrolyte
[0154] 36 positive electrode electrolyte
[0155] 38 Negative Electrolyte
[0156] 40 Storage Containers
[0157] 42 positive electrode chamber
[0158] 44 Negative chamber
[0159] 46Gel electrolyte layer for positive electrode
[0160] 48 Gel electrolyte layer for negative electrode
[0161] 50 porous sheets
[0162] 100 Aluminum Foil
[0163] 100a Aluminum foil substrate
[0164] 100b porous area
[0165] 100c Al-Li alloy layer
Claims
1. A separator for a lithium secondary battery, which is an aluminum foil, comprising an aluminum foil substrate having a porous region, The porous region is formed over the entire thickness direction of the aluminum foil substrate. The porous region has a plurality of continuous pores in which the pores are intricately connected in the thickness direction.
2. The separator for lithium secondary battery according to claim 1, wherein The Al—Li alloy exists in the porous region. 3 . The separator for a lithium secondary battery according to claim 1 , comprising an Al—Li alloy layer disposed on one or both surfaces of the aluminum foil substrate so as to cover the porous region. 4 .
4. The separator for lithium secondary battery according to claim 1 or 2, wherein The average pore diameter of the porous region is in the range of 0.00001 μm to 10 μm. 5 . A lithium secondary battery comprising: a positive electrode, a negative electrode, and the separator for a lithium secondary battery according to claim 1 provided between the positive electrode and the negative electrode, wherein the positive electrode and the negative electrode are separated from each other by the separator for a lithium secondary battery.
6. The lithium secondary battery according to claim 5, wherein: A gel electrolyte layer is provided between the positive electrode and the separator for a lithium secondary battery, and between the negative electrode and the separator for a lithium secondary battery.
Citation Information
Patent Citations
Separator and lithium secondary battery
JP1996180853A
Separator for battery, battery using this, vehicle using this, and battery mounted equipment
JP2010219012A
Rechargeable lithium-aluminum anode
US4002492A
Porous aluminum-foil cathode, preparation method of porous aluminum-foil cathode and lithium secondary battery
CN106654289A
Organic electrolyte cell
JP1989105464A